Pengaruh Digital Financial Literacy terhadap Financial Well-Being Melalui Financial Behaviour Studi pada Mahasiswa Manajemen Angkatan 2021 di Sidoarjo - Ivanka, Siska; Zaki, Achmad; Mustaqim, M.; Violita, Cynthia Eka (Universitas Syiah Kuala, 2025)
The purpose of this study is to determine the effect of Digital Financial Literacy on Financial Well-Being with Financial Behavior as a mediating variable. This study applies a quantitative method, a survey approach through the use of questionnaires in collecting data from respondents, with a non-probability sampling method. Management students from the 2021 class in Sidoarjo are the population. SmartPLS 4 serves as the primary tool for data analysis in this study. The results indicate that Digital Financial Literacy does not have a significant impact on Financial Well-Being, Financial Behavior has a positive impact on Financial Well-Being, Digital Financial Literacy has a positive impact on Financial Behavior, and Financial Behavior mediates the relationship between Digital Financial Literacy and Financial Well-Being.